Technology of bakery products with carotene-containing plant raw materials - Hryshchenko, Anna; Bondarenko, Yuliia; Hrabovskyi, Vladyslav (My University, 2021)
Structural-mechanical properties of wheat dough with the addition of carrot and pumpkin dried pomace have been studied. According to the results of a study of the quality of bread, it was found that carrot pomace should be added in an amount of 10% to the mass of flour, and pumpkin pomace in an amount of 5% to the mass of flour. Досліджено структурно-механічні властивості пшеничного тіста з додаванням морквяних та гарбузових сушених вичавок. За результатами дослідження якості хліба встановлено, що морквяні вичавки необхідно додавати в кількості 10 % до маси борошна, а гарбузові — 5 % до маси борошна.
Keywords: bread quality; carrot pomace; pumpkin pomace; dough; β-carotene; якість хліба; морквяні вичавки; гарбузові вичавки; тісто; β-каротин; кафедра технології хлібопекарських і кондитерських виробів